Comparative biotoxicity of N-Phenyl-1-naphthylamine and N-Phenyl-2-naphthylamine on cyanobacteria Microcystis aeruginosa. (June 2017) - Cheng, Long; He, Yan; Tian, Yun; Liu, Biyun; Zhang, Yongyuan; Zhou, Qiaohong; Wu, Zhenbin
Abstract: N-Phenyl-1-naphthylamine (P1 NA) and N-Phenyl-2-naphthylamine (P2 NA) are both widely used as antioxidant and plant secondary metabolites. In this study, growth, esterase, photosynthetic activity and cell membrane integrity were used as biomarkers to compare biotoxicity of P1 NA and P2 NA on Microcystis aeruginosa . According to the results, a dose-response relationship was observed only between P1 NA concentrations and growth inhibition. The EC50 (48 h) of P1 NA calculated from growth inhibition was 16.62 μM, while that of P2 NA was not detected. When the esterase and photosynthetic activity were applied to evaluate the biotoxicity, it was found that a concentration of 20 μM P1 NA, P2 NA caused reduction of esterase activity and Fv/Fm of M. aeruginosa to 22.2 and 3.3%, 97.5 and 92.1%, respectively, after 48 h exposure. The percentage of membrane-damaged cells was increased as P1 NA exposure concentration increased, but that was not detected when exposure to P2 NA. The difference substituted position in the molecular structure of P1 NA and P2 NA leads to different toxicological properties and only P1 NA was found highly toxic to M. aeruginosa . The toxicity is due to that only P1 NA can be biotransformed to 1, 4-naphthoquinone, which could induce overproduction of intracellular ROS as well as result in oxidative damage and growth inhibition of test organism. Highlights: P1 NA and P2 NA with similar molecular structure, only P1 NA was found high toxic to M. aeruginosa. ROS induced by P1 NA could the reason of the growth inhibition of M. aeruginosa. The formation of 1, 4-naphthoquinone was the key factor to generate excessive ROS.